(untitled) (Iraqi Journal of Medical Sciences, 2023)
Background: Ultrasonography of the pelvic floor, either by the trans-perineal or the endo-vaginal/introital approach, has been effectively utilized in the diagnostic workup of urinary incontinence. Anterior and posterior urethral angles, funneling of bladder neck, urethral hypermobility and bladder base position can be evaluated using pelvic floor ultrasonograph. Objective: To assess the impact of variability of ultrasound technique (transvaginal ultrasound; TVS, and transperineal; TPUS) on the measurement of the resting urethral angles in a sample of continent Iraqi women. Methods: This study included 100 healthy continent adult females, The numerical values of the urethral angles were obtained by both TVS and TPUS techniques in a sample of women attending Ultrasound Unit in Al-Imamein Al-kadhimein Medical City during 2017. Results: The ? angle mean of studied women measured by TVS was 91.92 while that measured by TPUS was 78.67 with highly significant difference between both techniques (p